SOSIALISASI RISIKO STROKE PADA LANSIA KELURAHAN BANE KOTA PEMATANG SIANTAR - Marolop Parlindungan Napitu; Isa Harpika Br. Ginting; Hendri, Hendri (Nusantara Hasana Journal, 2025)
This community service project aims to enhance elderly knowledge about stroke in Bane Village, Pematang Siantar, through direct education and pre-test/post-test evaluation. Methods involved a straightforward outreach approach using simple language, collaboration with local health volunteers, and adherence to health protocols during the activities. Approximately 20 elderly participants were assessed, focusing on defining stroke, major risk factors (hypertension, diabetes mellitus, heart disease, smoking, and physical inactivity), early signs and symptoms, and preventive steps through healthy lifestyle changes, regular health checkups, and the role of physiotherapy in prevention and functional recovery. Results indicated a significant improvement in elderly knowledge after the education session, with a shift from lower knowledge levels to higher categories. Discussion highlights the importance of collaboration among healthcare professionals, community health volunteers, and elderly participants to build a stronger community support network for stroke prevention. Practical implications include periodic health education sessions, training for health volunteers, integration of stroke education into broader community health programs, and leveraging senior-friendly digital media to broaden informational reach. This study supports the Tri Dharma of Higher Education by enhancing scholarly and service contributions that improve the quality of life for the elderly in the local community.